"Basnig" operation in Mercedes Camarines Norte. - Gonzales, Tomas S. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1952)
Hunting and fishing were the chief industries of the primitive people. Fishes were abundant during that time so that the people depended largely upon fishing for their means of livelihood. The fishing ground in Mercedes Bay has been of great value to the Filipinos, especially to the people of Mercedes who have derived much benefit from its fish and other aquatic product. It has contributed significantly to the progress of our fishing industry. The "bansig" is now considered as one of the most common and profitable gears employed in the fishing industry. At first the fishermen used only kerosene lamps called "hasag" with the masted banca to carry the boat to and invested for this outfit. As time progresses, improvements were made. The "hasag" were replaced by electric bulbs while the sailboat were replaced with powered vessel.
Keywords: Fish-Capture.